Análisis de la gestión de cobranza y su incidencia en la cartera vencida de los predios urbanos y rurales del Gobierno Autónomo Descentralizado Municipal - Ley Molina, Merisuet de Jesús (2022)
The purpose of this research work is to improve the collection management through an analysis of past due portfolio of the GAD municipality since it is important to generate their own financial resources, so that these can be reinvested in social works of benefit to community, therefore, the municipalities of the country must make enormous efforts to increase their self-management income, the maximization of tax revenues must acquire greater relevance in the municipal financial areas, since these represent sources of important income. To carry out the present investigation, a set of analyzes, observations of documents and questionnaires were used to a sample of the population, as well as public officials who work in the municipality, once with the results obtained, the conclusion was reached. That the GAD has a deficiency in the process of collecting taxes on urban and rural properties and a lack of tax culture among the inhabitants.